Hypoxia inducible factor signaling and experimental persistent pulmonary hypertension of the newborn - Wedgwood, Stephen; Lakshminrusimha, Satyan; Schumacker, Paul T.; Steinhorn, Robin H. (Frontiers in Pharmacology, 2015)
BACKGROUND: Mitochondrial reactive oxygen species levels and nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB) activity are increased in a lamb model of persistent pulmonary hypertension of the newborn (PPHN). These events can trigger hypoxia inducible factor (HIF) signaling in response to hypoxia, which has been shown to contribute to pulmonary vascular remodeling in rodent models of pulmonary hypertension. However the role of HIF signaling in chronic intrauterine pulmonary hypertension is not well understood. AIM: To determine if HIF signaling is increased in the lamb model of PPHN, and to identify the underlying mechanisms. RESULTS: PPHN was induced in lambs by antenatal ligation of the ductus arteriosus at 128 days gestation. After 9 days, lungs and pulmonary artery smooth muscle cells (PASMC) were isolated from control and PPHN lambs. HIF-1α expression was increased in PPHN lungs and HIF activity was increased in PPHN PASMC relative to controls. Hypoxia increased HIF activity to a greater degree in PPHN vs. control PASMC. Control PASMC were exposed to cyclic stretch at 1Hz and 15% elongation for 24h, as an in vitro model of vascular stress. Stretch increased HIF activity, which was attenuated by inhibition of mitochondrial complex III and NFκB. CONCLUSION: Increased HIF signaling in PPHN is triggered by stretch, via mechanisms involving mitochondrial ROS and NFκB. Hypoxia substantially amplifies HIF activity in PPHN vascular cells. Targeting these signaling molecules may attenuate and reverse pulmonary vascular remodeling associated with PPHN.